Comparing the Effect of Volume-controlled Ventilation and Synchronized Intermittent Mandatory Ventilation on Respiratory Parameters of Traumatic Brain Injury Patients - Wakeel, Kashif; Sharif, Zubair; Shah, Behramand; Ashfaq ur Rehman,; Rehman, Gauhar; Iqbal, Mohammad; Zia, Farhan (Indus Journal of Bioscience Research, 2025)
Introduction: Traumatic brain injury (TBI) often necessitates mechanical ventilation to support respiratory function. This study compares the outcomes of volume-controlled ventilation (VCV) and synchronized intermittent mandatory ventilation (SIMV) in TBI patients, focusing on respiratory and neurological outcomes. Materials and Methods: This study was conducted at Lady Reading Hospital in Peshawar, Pakistan from March 2024 to September 2024. A total of 100 TBI patients (50 VCV, 50 SIMV) were enrolled. Demographic data, including age, gender, BMI, smoking status, and comorbidities, were collected. Respiratory parameters (respiratory rate, tidal volume, PaO₂, PaCO₂, pH, SpO₂) were recorded at baseline and after 48 hours. Neurological outcomes were assessed using the Glasgow Coma Scale (GCS) at day 7. Statistical comparisons were made using t-tests and chi-square tests. Results: Demographic and clinical characteristics were similar between the VCV and SIMV groups. Baseline respiratory parameters showed no significant differences. After 48 hours, the VCV group had a lower respiratory rate (18.3 vs. 19.5 breaths/min, p = 0.03), higher PaO₂ (90.2 vs. 85.6 mmHg, p = 0.02), and more effective carbon dioxide elimination (PaCO₂ 37.0 vs. 39.1 mmHg, p = 0.01). Complications, such as ventilator-associated pneumonia, barotrauma, and oxygen toxicity, were comparable between groups. Neurological outcomes showed a trend toward improvement in the VCV group (48% vs. 34%, p = 0.14). Conclusion: VCV provided better respiratory outcomes than SIMV, with improved oxygenation and more efficient carbon dioxide elimination. Though both ventilation strategies had similar complication rates, VCV may offer a slight advantage in neurological recovery. Further research is needed to confirm these findings.